Penerapan Metode Kooperatif Tipe Learning Together Untuk Meningkatkan Hasil Belajar Seni Budaya di SMAN 8 Denpasar - Gusti Ayu Made Puspawati; Gusti Ayu Agung Trisna Prameswari; Mirah Rahmawati (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
After conducting initial observations at SMK Negeri 8 Denpasar, it was discovered that the students' learning outcomes in cultural arts subjects were relatively low. Therefore, the researcher decided to conduct further study using the PTK (Classroom Action Research) approach method. The aim of implementing the PTK method was to enhance students' understanding of the cultural arts subject through a cooperative learning model known as "learning together," with the goal of improving student learning outcomes. The PTK method involved 2 cycles, with each cycle consisting of 4 stages. The research subjects were the 35 students of class XII Mipa-4 at SMA Negeri 8 Denpasar. Data was collected using performance assessment and observation methods. The collected data was analyzed using a qualitative descriptive method, which aimed to examine the entire cultural arts learning process. Additionally, a qualitative method was applied to analyze the results of the assessment of student performance by comparing the average value of the completeness of learning outcomes. Following the analysis, it was observed that in cycle I, the highest and lowest scores for students of SMA Negeri 8 Denpasar class XII Mipa-4 were 85 and 60, respectively, with a class average score of 71. However, in cycle II, the highest and lowest scores increased to 95 and 80, and the class average score rose to 88. Furthermore, in cycle II, all students achieved scores above the minimum completeness level. This indicated a significant improvement in student scores from cycle I to cycle II.